2021
DOI: 10.1002/adfm.202106446
|View full text |Cite
|
Sign up to set email alerts
|

Trigger‐Detachable Hydrogel Adhesives for Bioelectronic Interfaces

Abstract: Recent electronics technology development has provided unprecedented opportunities for enabling implantable bioelectronics for long-term disease monitoring and treatment. Current electronics-tissue interfaces are characterized by weak physical interactions, suffering from potential interfacial failure or dislocation during long-term application. On the other hand, some new technologies can be used to achieve robust electronics-tissue interfaces; however, such technologies are limited by potential risks and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 39 publications
0
85
0
Order By: Relevance
“…Clear and tight interface between the hydrogel adhesive layer and artery tissue layer is observed, corroborating the tough and conformal interfacial bonding. The seamless interface could be interpreted by the dry crosslinking mechanism, [22,23] where the hydrogel dry film instantly swelled and drained the interfacial water immediately; afterward, the polymer chains promptly penetrated into the biological tissues, and further entangled and crosslinked with the biological tissues. [33,34]…”
Section: Ex Vivo Wound Sealingmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear and tight interface between the hydrogel adhesive layer and artery tissue layer is observed, corroborating the tough and conformal interfacial bonding. The seamless interface could be interpreted by the dry crosslinking mechanism, [22,23] where the hydrogel dry film instantly swelled and drained the interfacial water immediately; afterward, the polymer chains promptly penetrated into the biological tissues, and further entangled and crosslinked with the biological tissues. [33,34]…”
Section: Ex Vivo Wound Sealingmentioning
confidence: 99%
“…The tough and instant interfacial adhesion arose from the synergetic contribution from both noncovalent interactions (i.e., hydrogen bonding and electrostatic interactions) and covalent bonds between the NHS (adhesive side) and amine groups (tissue side) (Figure 1c). [22,23] Previously, a wide variety of hydrogel bioadhesives have been reported either from monomer precursors, [22,24,25] in situ gelation of functional polymer solution, [12,[26][27][28] biopolymer solutions (i.e., silk), [29][30][31] or DOPAinspired adhesives [31,32] (Table S1, Supporting Information). These systems represent strategies to construct hydrogel networks as bioadhesives, however, might be challenged by the residues of monomers or other small-molecule residues, which could induce undesirable immunological side-effects during the in vivo applications.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition and adhesion behavior of the polydopamine on different surfaces is not yet well understood. Zhang et al reported that the wettability has a significant influence on the adhesion and that hydrophobic surface enhances the PDA adhesion [56] When it comes to interfacial applications between components and tissues for the medical industry, the interfaces are often weak, which can lead to delamination during long-term implantation and biological sequelae. Within efforts to improve this problem, Xue et al designed and manufactured a hydrogel bio adhesive that is capable of instant and robust adhesion and enables release triggered by on-demand stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels stand at the middle of the podium when it comes specifically to sustaining release delivery because of their ability to provide spatial and temporal control over the release of drugs. The development of tuneable hydrogels such as in-situ forming, stimuli (pH, temperature and enzymes) responsive [ 3 , 4 , 5 ], fatigue resistant [ 6 , 7 ], mechanical tune-ability with nano-particulate crosslinkers [ 8 ] and the degradation controlled hydrogel matrices are mainly based upon their physicochemical properties [ 9 ]. Over the past few decades, studies on novel drug delivery systems in general, and hydrogels in particular, have been focused on the so-called biocompatible synthetic polymers, which have dominated the era because of their consistency and considerable purity.…”
Section: Introductionmentioning
confidence: 99%